2018
DOI: 10.1016/j.toxlet.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

High-mobility group box 1 protein-mediated necroptosis contributes to dasatinib-induced cardiotoxicity

Abstract: Dasatinib shows remarkable activity against imatinib-refractory chronic myelogenous leukemia (CML) and Philadelphia chromosome positive acute lymphoblastic leukemia (PhALL). However, severe cardiovascular toxicity limits the clinical applications of dasatinib. Since the underlying mechanism of dasatinib-induced cardiotoxicity is still elusive, we aim to clarify this. Recent studies have shown that necroptosis and apoptosis participate in multiple toxicity development. Here, we first report that dasatinib could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Moreover, the Nec-1 administration also reduced protein leakage that indicated impaired cellular membrane and the formation of inflammatory mediators. HMGB1, a well-recognized necroptosis marker [ 36 ] was significantly increased in the BAL fluid following IR and could be reduced by Nec-1 but not z-VAD-fmk treatment. These data supported the contribution of necroptosis to lung IR injury, and this was consistent with the results by Kanou T et al, who demonstrated that the Nec-1 administration to both donor and recipient could significantly inhibit necrotic cell death and improve graft function following lung transplantation in rats [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the Nec-1 administration also reduced protein leakage that indicated impaired cellular membrane and the formation of inflammatory mediators. HMGB1, a well-recognized necroptosis marker [ 36 ] was significantly increased in the BAL fluid following IR and could be reduced by Nec-1 but not z-VAD-fmk treatment. These data supported the contribution of necroptosis to lung IR injury, and this was consistent with the results by Kanou T et al, who demonstrated that the Nec-1 administration to both donor and recipient could significantly inhibit necrotic cell death and improve graft function following lung transplantation in rats [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cell survival was assessed with a sulforhodamine B colorimetric assay (SRB, #S1402, Sigma) [24]. Briefly, cell monolayers were fixed with 10% (wt/vol) trichloroacetic acid and stained for 30 min, after which the excess dye was removed by washing repeatedly with 1% (vol/vol) acetic acid.…”
Section: Cell Survival Assaymentioning
confidence: 99%
“…Quantitative real-time polymerase chain reaction analysis The quantitative polymerase chain reaction (qPCR) analysis was performed as described previously [24]. Total RNA isolation was carried out with an RNAiso Plus kit (#9109, TaKaRa, Japan) according to the manufacturer's instructions.…”
Section: Intracellular Gsh Concentration Determinationmentioning
confidence: 99%
“…The DAMPs that are secreted/released upon necroptosis include: (I) "find me" signals (as described above); (II) intracellular chaperones such as heat-shock proteins (HSPs) [160] and S100 protein family members; (III) alarmins or cytokine-like DAMPs [161] and (IV) nucleic acids (nuclear or mitochondrial DNA) [162]. One of the most ubiquitous alarmins released during necroptosis is the high mobility group box 1 (HMGB1) protein [63,163,164]. These DAMPs usually stimulate the initial sensors of infection or damage, i.e., PRRs on myeloid cells, thereby efficiently co-stimulating them and enabling a better interface between these activated myeloid cells and adaptive immune cells [165].…”
Section: Necroptosis-driven Modulation Of Immune Responsesmentioning
confidence: 99%